2008
DOI: 10.1080/08934210802305028
|View full text |Cite
|
Sign up to set email alerts
|

The Legitimization of Paltry Favors Effect: A Review and Meta-Analysis

Abstract: A meta-analysis was conducted on the legitimization of paltry favors (LPF) effect (Cialdini & Schroeder, 1976). A total of 19 studies met the inclusion criteria, with a combined sample of 2,730 subjects. Excluding studies in which the LPF request was delivered via mail and those studies that accepted pledges as the dependent variable resulted in a homogeneous set of effect sizes (r ¼ .18, OR ¼ 2.41). While the data provide clues as to possible mediating mechanisms, the cause of the effect is still not clear. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 21 publications
4
35
2
Order By: Relevance
“…Most research conducted on the LPF effect utilized the context of fundraising, with LPF tags being added to requests for monetary donations (e.g., ''Even a penny would help''). Thus, most of the studies appearing in the Andrews et al (2008) meta-analysis featured fundraising efforts. Although Andrews et al revealed a nonzero average effect for the LPF, the magnitude of this average effect seems small enough as to leave open the question about the extent to which this strategy feasibly generalizes to other compliance-gaining situations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most research conducted on the LPF effect utilized the context of fundraising, with LPF tags being added to requests for monetary donations (e.g., ''Even a penny would help''). Thus, most of the studies appearing in the Andrews et al (2008) meta-analysis featured fundraising efforts. Although Andrews et al revealed a nonzero average effect for the LPF, the magnitude of this average effect seems small enough as to leave open the question about the extent to which this strategy feasibly generalizes to other compliance-gaining situations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review and meta-analysis of the LPF (Andrews et al, 2008) reveals modest gains in compliance when using the technique (weighted r ¼ .11). Since Cialdini and Schroeder's (1976) seminal work, several studies have replicated the effect, tested the LPF's boundary conditions, probed for mediators and moderators, and identified explanatory mechanisms (e.g., Dolinski, Grzyb, Olejnik, Prusakowski, & Urban, 2005;Perrine & Heather, 2000;Reeves, Macolini, & Martin, 1987;Reeves & Saucer, 1993;Shearman & Yoo, 2007;Takada & Levine, 2007).…”
Section: Explaining the Legitimization Of Paltry Favors Effectmentioning
confidence: 96%
See 3 more Smart Citations